METHODOLOGICAL PROBLEMS OF RESEARCH IN HISTORY OF PHYSICAL CULTURE OF XX CENTURY IN THE TERRITORY OF FORMER YUGOSLAVIA - Slađana Mijatović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The entire XX century has passed in turbulent political and economic changes in the entire world, and especially in Europe. This was particularly expressed on the terri- tory of the Kingdom of Yugoslavia and Socialist Federal Republic of Yugoslavia (SFRY), were a few independent states were created at the beginning of XX century. All these changes reflected also in the field of culture and science and created ob- stacles for many cultural events, and especially scientific researches of certain phenome- na in these territories at the beginning of the XXI century. These difficulties will continue to be present for many years because the SFRY was disintegrated in wars, violence and crimes resulting in impossibility to establish faster normal collaboration between the newly created states. This problem has not speared even the researches in history of physical culture of the XX century on the territory of former SFRY, because no normal communication bet- ween some of the newly formed states has been established, so the access to researches of primary historic resources, which is necessary in heurictc phase, is lacking. Therefore it is necessary to establish collaboration between colleagues-resear- chers from these territories, more that usually in order to create possibilities for valid researches with objective and worthy conclusions